A zinc(II) amidine complex: tandem synthesis, structure, and self assembly. Issue 1 (2nd January 2016) - Roy, Sumit; Bhattacharya, Satavisha; Chattopadhyay, Shouvik
Abstract: A five-coordinate zinc(II) amidine complex, [Zn(DEP)(N3 )2 ] (DEP = N′-(2-(diethylamino)ethyl)picolinamidine), has been synthesized with 2-cyanopyridine and sodium azide in the presence of zinc(II) acetate dihydrate. The structure of the complex is confirmed by single-crystal X-ray diffraction analysis. The complex crystallizes in triclinic space group P -1 with cell dimensions a  = 7.486(5) Å, b  = 7.678(5) Å, c  = 14.480(5) Å, α  = 96.697(5)°, β  = 90.282(5)°, and γ  = 95.716(5)°. The hydrogen bonding interactions in the complex lead to the formation of a 2-D supramolecular network. The complex shows fluorescence with lifetime ~4 ns. Abstract :